DOMESTIC VIOLENCE IN INDIA: AN ANALYSIS - Prof. Prabir Kumar Pattnaik , Rubi Talukdar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Domestic violence is a global problem that reaches socioeconomic, cultural, racial and class distinctions across national borders. This problem is not only widely dispersed geographically, but it also has an extensive incidence which makes it a typical and accepted behavior. Domestic abuse us common, profoundly rooted and has significant implications for the health and wellbeing of women. Its existence remains morally indefensible. The cost to people, health care systems and society is high. The goal of this study is to report the prevalence of different types of domestic violence against women, to examine data on domestic violence against women in India and some suggestive interventions. Managing domestic abuse incudes basically a joint effort of law enforcement, social security, and health services. Although efforts have been made in this direction, the cases attended represent only the tip of the iceberg, as most cases are not reported due to family member social pressures or defamatory social stigma. Real change these cases can only be bought about by changing the mindset of society through education and better law enforcement.